A new species of Hypostomus Lacepède, 1803 (Siluriformes: Loricariidae) from the Mearim River basin, northeastern Brazil - de Oliveira, Rafael Ferreira; Guimarães, Erick Cristofore; De Brito, Pâmella Silva; Ottoni, Felipe Polivanov (Zootaxa, 2022)
Hypostomus krikati sp. n. is described from the Mearim River basin, state of Maranhão, northeastern Brazil. This new species shares all the diagnostic features defining the Hypostomus plecostomus super-group. Three species of the H. plecostomus super-group are geographically close to the species described here (Hypostomus jaguribensis, H. pusarum and H. papariae). Hypostomus krikati sp. n. is easily distinguised from them by having conspicuous keels along the lateral series of plates. There are other species geographically close to H. krikati sp. n. that do not belong to the H. plecostomus super-group (H. johnii, H. velhomonge and H. velhochico). Hypostomus krikati sp. n. differs from these species by having a lower number of teeth, conspicuous keels along the lateral series of plates, abdominal region totally covered by plates, dark spots horizontally not aligned along lateral series of plates, and large-sized adults. The recently described species for the Maranhão hydrographic systems, as well as the new species here described reinforce the hypothesis that the Maranhão hydrographic systems may present a high level of endemism for freshwater fishes.